PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Dominikus Octavianto Kresno Widagdo; Anis Chariri (Diponegoro Journal of Accounting, 2014)
Company’s performance can be seen in several indicators such as Earning Per Share. This indicators can be used as a guideline for investor to assess the company’s performance. However, not all of the information that stated in financial statement was stated properly. In the company that their corporate governance is not running well, could make gap between information that stated in financial statement and fact that happen in company. Corporate governance mechanism is expected to minimize the agency problem, so the company’s performance can be increase. The purpose of this study is to analyze the effect of corporate governance mechanism on company’s performance.The population in this study are all non financial companies listed on the Stock Exchange in 2012. The sampling method used in this study was purposive sampling method.The total number of samples in this study were 89 research samples. This study used multiple linear regression as analysis instrument. Before doing the regression test, it’s examined by using classical assumption test. The results of this study indicate that the independence of the audit committee , the independence of the board of commissioners , managerial ownership , the number of commissioners meeting , and the number of audit committee meetings do not affect the performance of the company . From this study, only board size is significant positive effect on firm performance .